Amino functionalization optimizes potential distribution: A facile pathway towards high-energy carbon-based aqueous supercapacitors. (November 2019) - Yu, Minghao; Wang, Zifan; Zhang, Haozhe; Zhang, Panpan; Zhang, Tao; Lu, Xihong; Feng, Xinliang
Abstract: Resolving the mismatch between the practical potential window (PPW) and the available capacitive potential window of supercapacitor electrodes provides a feasible way to expand the operating voltage of supercapacitors, which further boosts energy density. Here, our research unveils a unique approach to manually control the PPW of the corresponding carbon-based supercapacitors (CSCs) by rational functionalization with amino groups. The extra pair of electrons from amino N atoms naturally adsorbs cations in the electrolyte, which rationalizes the surface charge of the carbon electrode and adjusts the PPW. A remarkable voltage expansion is achieved for CSCs, from 1.4 V to its maximum limit, 1.8 V, correspondently resulting in an approximately 1-fold increase in the energy density. Importantly, such a simple strategy endows our CSCs with an outstanding maximum energy density of 7.7 mWh cm −3, which is not only among the best values reported for thin-film CSCs but also comparable to those reported for Li thin-film batteries. These encouraging results are believed to bring fundamental insights into the nature of potential control in energy storage devices. Graphical abstract: A facile pathway to control the practical potential windows of carbon-based supercapacitors is unveiled by rational functionalization with amino groups. The proposed strategy enables a remarkable voltage expansion, from 1.4 V to its maximum limit, 1.8 V, correspondently resulting in the doubled energy density for our carbon-based supercapacitors. Image 1 Highlights: A voltage expansion strategy is revealed for carbon-based aqueous supercapacitors. The voltage is expanded from 1.4 to 1.8 V with a 1-fold increase in energy density. The electrochemical study and DFT calculation disclose the underlying mechanism. The generality of employing amino groups to expand the voltage is demonstrated.